2016
DOI: 10.4081/ejh.2016.2711
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dissection is associated with reduced polycystin-1 expression, an abnormality that leads to increased ERK phosphorylation in vascular smooth muscle cells

Abstract: The vascular smooth muscle cell (VSMC) phenotypic switch is a key pathophysiological change in various cardiovascular diseases, such as aortic dissection (AD), with a high morbidity. Polycystin-1 (PC1) is significantly downregulated in the VSMCs of AD patients. PC1 is an integral membrane glycoprotein and kinase that regulates different biological processes, including cell proliferation, apoptosis, and cell polarity. However, the role of PC1 in intracellular signaling pathways remains poorly understood. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(29 reference statements)
0
10
0
3
Order By: Relevance
“…In our study, we found that the MEK–ERK1/2 signaling pathway and ATG5 and ATG7 were regulated by EZH2 at the same time, and we also did not rule out the possibility of MEK–ERK1/2 signaling regulating ATG5 and ATG7 expression or their interaction in VSMCs. On the other hand, recent studies have shown that the MEK–ERK1/2 signaling pathway is also a contributor to other pathophysiological processes of AD, including VSMC phenotype switch 39 , apoptosis 40 , and proliferation inhibition 41 . Although we have demonstrated that EZH2 has no effects on VSMC apoptosis and proliferation, whether EZH2 could regulate VSMC phenotype switch via MEK–ERK1/2 signaling remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the MEK–ERK1/2 signaling pathway and ATG5 and ATG7 were regulated by EZH2 at the same time, and we also did not rule out the possibility of MEK–ERK1/2 signaling regulating ATG5 and ATG7 expression or their interaction in VSMCs. On the other hand, recent studies have shown that the MEK–ERK1/2 signaling pathway is also a contributor to other pathophysiological processes of AD, including VSMC phenotype switch 39 , apoptosis 40 , and proliferation inhibition 41 . Although we have demonstrated that EZH2 has no effects on VSMC apoptosis and proliferation, whether EZH2 could regulate VSMC phenotype switch via MEK–ERK1/2 signaling remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that MYC was indeed upregulated in ATAAD [ 52 ]. MYC signaling is involved in vascular smooth muscle cell (VSMC) dysfunction, vasoconstriction, and vascular remodeling in aortic dissection [ 53 ]. ITGA2 interacts with collagen in tumors, promotes cell migration, and promotes apoptosis-free resistance [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…We for the first time showed that crocin suppressed ERK1/2 pathway in cultured VSMCs. The role of ERK1/2 and KLF4 in VSMCs phenotypic switch had been well established ( 32 35 ). We also revealed that ERK1/2 inhibitor U0126 significantly reduced p-ERK1/2 and KLF4 levels.…”
Section: Discussionmentioning
confidence: 99%